The impact of performance management on Moletele Communal Property Association's performance at Maruleng Local Municipality of the Limpopo Province - Masoga, Morongwa Virginia (University of Limpopo (Turfloop Campus), 2013)
Recent changes in the allocation of land through the results of land redistribution have compelled members of communities to form committees, that is, Communal Property Associations (CPAs) that would be responsible for managing the claimed land. The Maruleng Local Municipality was not excluded from this process. Five of the CPAs have been formed under the above mentioned municipality to manage claimed land. The research investigated the impact of performance management on the Moletele CPA’s performance at Maruleng Local Municipality of the Limpopo Province. The management of Moletele CPA was not without challenges, problems such as lack of resources, adequate training programmes, lack of clear policy and objectives were also found in the study. This research also seeks to investigate why Moletele CPA is performing better than the other CPAs in the municipality. In order to understand the total context of the challenges faced by Moletele CPA, an empirical research and interviews were conducted to collect data from the members of Moletele CPA. The findings of the study suggest that a lack of resources and relevant training programmes are contributing negatively towards the performance of the Moletele CPA in particular, and other CPAs in general. To conclude, the study revealed that performance management is not determined by one factor, but other challenges such as clarity of policies and cooperation amongst stakeholders also contribute towards the success of the Moletele CPA ;hence the recommendations made in chapter five.
Thesis (M. Dev.) -- University of Limpopo, 2013
Keywords: Performance management; Land redistribution; 658.3125; Perfromance -- Management; Performance standards; Employees -- Rating of